IMPLEMENTASI KEEFEKTIFAN ORGANISASI: Studi Kritis dinamika Prilaku Organisasi PendidikanTinggi Islam (Matrikulasi) - Zainur Arifin; Sulistyorini (Muróbbî: Jurnal Ilmu Pendidikan, 2021)
Abstract: The effectiveness of the organization in Islamic higher education institutions is a community demand and need that cannot be negotiated. Therefore Islamic universities are obliged to manage their institutions to produce smart, skilled, civilized and cultured students. Education not only seeks to improve knowledge, but also can produce scientists and intellectuals who have faith, devotion, and personality. Organizations in Islamic higher education institutions discuss the implementation of leading and controlling in Islamic higher education institutions, the implementation of decision making and policy making of Islamic higher education institutions and the implementation of internal and external evaluators in assessing student achievement. Researchers make improvements. There are several possibilities that must be considered, namely the availability of adequate time allocation, rationalization of additional employees and / or equipment, sufficient time allocation for managers to make management improvements and the extra effort of all existing components. These Islamic higher education institutions tend to look more oriented and focused on education and its processes. Educational inputs such as infrastructure, and the curriculum and processes, are very important for one's success in learning, but this is not enough. Therefore, to improve the situation above, the effectiveness of educational organizations in Indonesia must now begin to focus on controlling the quality of graduates.